The Crimea conundrum: legitimacy and public opinion after annexation. Issue 1 (2nd January 2019) - O'Loughlin, John; Toal, Gerard
ABSTRACT: The widespread international condemnation of the annexation of Crimea by Russia in March 2014 is at odds with the strong local support for the transfer of territory in the peninsula. Though regarded as illegitimate by most governments as indicated in a UN General Assembly vote, the Russian government argued that the transfer was justified since it reflected the majority opinion in Crimea. The examination of attitudes in December 2014 through a representative survey in Crimea confirmed the support for territorial transfer and indicated that most residents believed that their well-being would improve as a result. Most lamented the end of the Soviet Union but strongly trusted President Putin and his policies as a way to improve the local economy. Nearly everyone had Russian citizenship less than a year after the annexation. There was little difference between the biggest demographic groupings, Russians and Ukrainians, in attitudes and beliefs. Exceptionally, the Tatar minority consistently demonstrated opposition to the annexation, distrust of Putin and supported a return to the circumstances that the peninsula had experienced after 1991. With the exception of this minority, the annexation continues to garner wide popular approval despite international opprobrium, sanctions against Russia and sustained geopolitical tensions in the Black Sea region. This is the Crimea conundrum.